Consumer Intention in Using Mobile Banking Services: Using Extended TAM Model - Parajuli, Rishi Kanta (Madhyabindu Journal, 2023)
Nepalese banks are using modern technologies to prompt their services and enlarging customer satisfaction. Realizing this fact, this study aims to identify different factors impacting on behavioral intention to use mobile banking. Extended Technology Acceptance Model was used to extract constructs and validate the findings. This study is based on descriptive analytical research design. A survey of 200 banking customers was done in Kawasoti Municipality, Nepal. Structured questionnaire was used to collect primary data and collected data was analyzed using IBM SPSS 20 version. It was found that perceived ease of use, perceived usefulness, trust and facilitating condition statistically affect behavioral intention to use mobile banking. The result of this study facilitates mobile banking providers for advancing different strategies that help for expanding the usage rate of mobile banking by current users and converting non users in to users.